Title does matter : a cross-sectional study of 30 journals in the Medical Laboratory Technology category - Njire Bratičević, Marina (Array, 2020)
Introduction: First impression on potential readers is created by the title; therefore, authors should give importance to the title structure. The aim of this study was to establish whether articles created by a smaller number of authors and with shorter, descriptive or declarative titles gain more citations and whether article title length and number of authors correlate to the number of citations.Material and methods: A cross-sectional study on article citation data for 30 scientific journals published in 2016 in Medical Laboratory Technology field according to Web of Science database was conducted. The type of article, type of title, as well as number of words in the title and number of authors was recorded.Results: In the group of original articles (N = 2623), articles with declarative titles (N = 336, 13%) showed statistically higher number of citations in multiple comparison analysis when compared to descriptive titles (P <0.001). No correlation was found between number of citations and title word count (r = 0.07, P <0.001) nor between number of citations and number of authors in group of original articles (r = 0.09, P <0.001). Original articles with descriptive titles longer than 15 words or with more than six authors are cited more (P = 0.005 and P <0.001, respectively).Conclusion: Based on results of our study, titles do matter. Therefore, authors of original articles might want to consider including their findings in the title and having longer titles.